A disposable polyurethane glove capable of being efficiently and stably produced in an industrial manner and a preparation process thereof
Patent Information
- Application Number
- CN202311569768.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-23
AI Technical Summary
[0052]与现有技术相比,本发明的有益效果主要体现在以下方面:
Smart Images

Figure BDA0004565065540000141
Abstract
Description
Technical Field
[0001] This invention relates to the field of disposable protective gloves, and more particularly to disposable polyurethane gloves that can be produced efficiently and stably in industrial settings, as well as their preparation method. Background Technology
[0002] Disposable protective gloves are closely related to our production and daily life. Nitrile gloves, latex gloves, and PVC gloves are currently the three main types of disposable gloves. These gloves each have their own characteristics and are used in various fields based on their performance advantages. Disposable polyurethane gloves, as a rising star, have distinct characteristics, such as being soft yet strong, having good skin-friendly breathability, and being free of sulfur, chlorine, and heavy metal residues. However, during the production of polyurethane gloves, problems such as edge curling and cracking are prone to occur. In normal production, crosslinking agents are usually introduced into the water-based latex. However, the presence of crosslinking agents shortens the activation period of the water-based latex, affecting the stability of the emulsion. Furthermore, during filtration and washing, because the crosslinking has not been cured, a large amount of curing agent migrates into the water due to concentration differences and is lost, thus reducing the effective utilization rate. Therefore, the stability problem of water-based latex is one of the unfavorable factors causing the inefficient and unstable production of polyurethane gloves. Summary of the Invention
[0003] To address the problems existing in the prior art and achieve efficient and stable production of polyurethane gloves, this invention innovatively introduces a crosslinking agent into the flocculant system, which then adheres to the hand mold. This ensures the stability of the water-based latex, reduces cracking, and improves the pass rate. It also reduces the migration of the crosslinking agent into the aqueous phase.
[0004] To achieve its purpose, the present invention adopts the following technical solution:
[0005] In a first aspect, the present invention provides a polyurethane composition comprising:
[0006] (1) Flocculant raw materials, by weight, include:
[0007] Release agent 1-6 parts, for example 1 part, 3.5 parts, etc.;
[0008] 5-20 parts of coagulant, for example, 8 parts, 10 parts, 12 parts, 18 parts, etc.;
[0009] 4-15 parts of crosslinking agent, such as 6 parts, 9 parts, 12 parts, etc.;
[0010] 55-81 parts pure water, such as 65 parts, 75 parts, etc.;
[0011] (2) Water-based latex raw materials, by weight, include:
[0012] Waterborne polyurethane, 40-60 parts, such as 41 parts, 45 parts, 50 parts, etc.;
[0013] Water 40-60 parts, for example 45 parts, 55 parts, etc.;
[0014] (3) Anti-stick coating, by weight, includes:
[0015] 5-10 parts of anti-sticking mortar, such as 6 parts, 8 parts, etc.;
[0016] Use 75-95 parts water, for example, 80 parts, 90 parts, etc.
[0017] In a preferred embodiment of the present invention, the flocculant raw material further comprises, by weight: 0.02-0.1 parts of wetting agent (e.g., 0.04 parts, 0.06 parts, 0.08 parts, etc.) and / or 0.01-0.15 parts of defoamer (e.g., 0.05 parts, 0.1 parts, etc.).
[0018] Preferably, the defoamer is selected from one or more of mineral oil-based defoamers and surfactant-based defoamers. For example, the defoamer is selected from one or more of Sangjing Chemical DF-677, Sangjing Chemical DF-38, and Shanghai Huiyan HY-6818.
[0019] In a preferred embodiment of the present invention, the release agent in the flocculant raw material is selected from one or more of paraffin-based release agents, calcium stearate-based release agents, and high-molecular-weight organosilicon-based release agents. For example, the release agent is selected from one or more of Keim-Additec E-342 (Germany) and Foshan Weiwei SD-6.
[0020] In a preferred embodiment of the present invention, the coagulant in the flocculant raw material is selected from one or more of calcium nitrate, calcium chloride and aluminum nitrate.
[0021] In a preferred embodiment of the present invention, the crosslinking agent in the flocculant raw material includes, but is not limited to, etherified amino resin, aziridine, carbodiimide, blocked isocyanate curing agent, etc., preferably one or more of the amino resin crosslinking agents CYMEL-385 and CYMEL-325 from Cytec Corporation. For example, the crosslinking agent is selected from one or more of CYMEL-385 and CYMEL-325 from Hydrotec Corporation.
[0022] In a preferred embodiment of the present invention, the aqueous latex raw material further comprises, by weight: 0.02-0.15 parts of color paste (e.g., 0.05 parts, 0.1 parts, etc.), 1-5 parts of titanium dioxide paste (e.g., 2 parts, 4 parts, etc.), and 0.02-0.1 parts of wetting agent (e.g., 0.04 parts, 0.06 parts, 0.08 parts, etc.).
[0023] In a preferred embodiment of the present invention, the waterborne polyurethane in the waterborne latex raw material is an aliphatic waterborne polyurethane and / or an aromatic waterborne polyurethane. Preferably, the solid content of the waterborne polyurethane is 30-50%, for example 35%, 40%, 45%, etc.
[0024] More preferably, the isocyanate used in the preparation of the waterborne polyurethane is selected from one or more of 4,4'-dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), and toluene diisocyanate (TDI); the polyol is selected from one or more of 1,6-hexanediol phthalic anhydride polyester polyol, polybutylene adipate, polypentyl adipate, and polycarbonate diol. More preferably, the number average molecular weight of the polyol is 800-3000 Daltons, for example, 1000 Daltons, 1500 Daltons, 2000 Daltons, 2500 Daltons, etc.
[0025] For example, the waterborne polyurethane in the waterborne latex raw material is selected from: Wanhua Chemical. 7566、 7351 3458、 3978 and 3979.
[0026] In a preferred embodiment of the present invention, the colorant in the aqueous latex raw material is a blue colorant, a black colorant, or a green colorant. For example, the colorant is selected from S19-LR03 of Shiming.
[0027] In a preferred embodiment of the present invention, in both the flocculant raw material and the aqueous latex raw material, the wetting agent is independently selected from one or more nonionic surfactant wetting agents. For example, the wetting agent is one or more of TERIC-320 and ETAID ST-1865.
[0028] In a preferred embodiment of the present invention, the anti-stick coating material is selected from one or more of waterborne polyurethane or waterborne acrylic glove inner coatings. For example, the glove inner coating is selected from YMT-D2103 of Umet (Beijing) Environmental Materials Technology Co., Ltd., WF-78-123 of Stahl, etc.
[0029] In another aspect of the invention, the use of the above-described composition in the manufacture of gloves is discussed.
[0030] In another aspect of the invention, there is a method for preparing a glove, comprising the following steps:
[0031] S1, formulated with a combination of flocculant, water-based latex, and anti-sticking coating.
[0032] S2, clean the hand mold, impregnate with flocculant and dry.
[0033] S3, water-immersed resin tank
[0034] S4, inlet filter tank and dip coating tank
[0035] S5, after curling, enter the oven for curing and crosslinking.
[0036] S6, demolding.
[0037] In one specific implementation, the following steps are included:
[0038] 1) Add the flocculant raw material of the above composition to material tank A and keep stirring; add the water-based latex raw material to material tank B and keep stirring; add the anti-stick coating raw material to material tank C and keep stirring.
[0039] 2) After cleaning the hand mold, put it into the oven D for baking. After it comes out of the oven, cool it down to a certain temperature and immerse it in the material tank A to keep it moving forward steadily. After exiting the material tank A, the hand mold moves into the oven D for baking.
[0040] 3) After the hand mold finishes baking in oven D, it is cooled down and then immersed in material tank B to maintain stable operation. After exiting material tank B, the hand mold moves to oven D for baking. After baking until the film is surface dry, it moves into filtration tank E to maintain stable operation. After exiting filtration tank E, the hand mold moves to oven D for baking.
[0041] 4) After the hand mold is baked in oven D, it is immersed in material tank C and kept running smoothly. After exiting material tank C, the hand mold moves to oven D for baking. After baking, the edges are rolled up and it continues to run into oven F for baking.
[0042] 5) After the hand mold is baked in oven F, it continues to be immersed in expansion tank G. After exiting tank G, it is demolded, washed with pure water to remove dust, dried, and then packaged into boxes.
[0043] In a preferred embodiment of the present invention, in step 1), the stirring rate is 300-500 r / min, for example 400 r / min.
[0044] In a preferred embodiment of the present invention, in step 2), the hand mold cleaning includes: acid tank brush cleaning, alkali tank brush cleaning, clean water tank brush cleaning, and scalding the mold in a clean water tank at 70-90°C; preferably, the acid tank contains a 2-8 wt% nitric acid aqueous solution, the alkali tank contains a 3-8 wt% sodium hydroxide aqueous solution, and the temperatures of the acid tank, alkali tank, and clean water tank are each independently 60-90°C.
[0045] In a preferred embodiment of the present invention, in step 2), the temperature of oven D is 50-100°C, the baking time in oven D before the hand mold enters material tank A is 1-5 min, the temperature when the hand mold is immersed in material tank A is 50-75°C, the total running time in material tank A is 5-15 s, and the baking time in oven D after exiting material tank A is 1-5 min.
[0046] In a preferred embodiment of the present invention, in step 3), the temperature of the hand mold when immersed in the material tank B is 50-75°C, the total running time in the material tank B is 15-35s, the baking time in the oven D after exiting the material tank B is 1-5min, the total running time in the filtration tank is 10-60s, and the baking time in the oven D after exiting the filtration tank is 1-5min; preferably, the filtration tank has cooling and heating functions, is filled with pure water, the number of filtration tanks is 2-5, and the water temperature is independently set to 50-70°C, and the calcium ion content of each filtration tank is kept below 1000ppm.
[0047] In a preferred embodiment of the present invention, in step 4), when immersed in the material tank C, the liquid level is 1-2 cm lower than the film. The total running time in the material tank C is 3-10 s, and the baking time in the oven D is 1-5 min, with the edge rolled up to the position of the coating. The temperature of the oven F is set to 120-145℃. Preferably, the baking in the oven F adopts a stepped temperature setting with a temperature gradient of 5-20℃, and the total baking time in the oven F is 25-30 min.
[0048] In a preferred embodiment of the present invention, in step 5), the expansion tank G is a pure water tank.
[0049] In a particularly preferred embodiment, the temperature of oven D in steps 3) and 4) is the same as the oven temperature in step 2).
[0050] In a preferred embodiment of the present invention, in step 5), after demolding, the product is washed with water to remove dust, dried, and subjected to an air leakage test. After passing the test, it is packaged.
[0051] In a further aspect of the invention, the invention relates to gloves obtained by the above-described glove preparation method.
[0052] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:
[0053] 1) In the field of disposable gloves, especially polyurethane gloves, the addition of crosslinking agents to flocculant raw materials can effectively reduce cracking and latex demulsification problems, and ensure stable operation of the production line.
[0054] 2) The crosslinking agent used in this invention is preferably an amino resin crosslinking agent. This crosslinking agent is used in small amounts and can effectively improve the chemical resistance of gloves. It is cheaper and consumes less energy compared to other types of crosslinking agents.
[0055] 3) During the glove molding process, residual calcium ions between the glove and the mold will seriously affect the feel and physical properties of the glove. In the leaching process of the present invention, calcium ions can be efficiently migrated from the inside of the glove to the leaching tank through the concentration gradient. The polyurethane gloves obtained by the composition and / or method of the present invention have a smooth feel, are comfortable to wear, skin-friendly, soft and elastic and easy to wear. Detailed Implementation
[0056] The present invention will be described in further detail below, but the invention is not limited thereto.
[0057] raw material
[0058] (1) Flocculant raw materials
[0059] Release agent: Foshan Weiwei SD-6, calcium stearate release agent;
[0060] Coagulant: Calcium nitrate, Shanghai Aladdin Biochemical Technology Co., Ltd., analytical grade 99%;
[0061] Crosslinking agent: CYMEL-385 from Hydrotech, Inc. (USA), a water-soluble amino resin crosslinking agent with 80% solids content;
[0062] Wetting agent: TERIC-320, a nonionic surfactant;
[0063] Defoamer: Sangjing Chemical DF-38, a surfactant-based defoamer;
[0064] (2) Water-based latex raw materials
[0065] Waterborne polyurethane:
[0066] Wanhua Chemical 7566 is an anionic aliphatic waterborne polyurethane with a solid content of 35%. The isocyanate is isophorone diisocyanate (IPDI), and the polyol is 1,6-hexanediol phthalic anhydride polyester polyol, manufactured by Stepan, with the brand name PH56 and a number-average molecular weight of 2000 Daltons.
[0067] Pigment: Shih Ming Blue Pigment S19-LR03;
[0068] Titanium dioxide paste: Shiming titanium dioxide paste, 70% solids content;
[0069] Wetting agent: TERIC-320, a nonionic surfactant;
[0070] (3) Raw materials for anti-stick coating
[0071] Anti-sticking paste: YMT-D2103 from Umet (Beijing) Environmental Materials Technology Co., Ltd.;
[0072] Unless otherwise specified, all other ingredients mentioned in this article are commercially available.
[0073] Test methods
[0074] Check for cracks: Check for holes or cracks at the junction of the thick and thin edges of the rolled edge;
[0075] Whether it slides down: Immerse the hand mold in the water-based resin glue tank at the same height, and check whether the glue film is lower than the immersion height after the glue is lifted. If it is lower than the immersion height, it is judged as sliding down.
[0076] Operational stability: The glove production line is operating normally. On the 3rd, 6th and 9th days of operation, 2 kg of latex was taken from material tank B, and the surface of the liquid was observed to form a skin. The latex was then filtered and weighed.
[0077] Resilience: Cut a sample finger of the same thickness, stretch it to the same length, hold it for 5 seconds, and observe the time required to return to the original shape. The rebound is judged by the length of time. A shorter time indicates a better rebound, and a longer time indicates a poorer rebound.
[0078] Ease of demolding: Rating based on the ease of removing the molded film from the hand mold, with 5 points being the best, indicating very easy demolding and 1 point being the worst, indicating very difficult demolding.
[0079] Thickness: Cut glove strips from the same area and measure the thickness using a high-precision film thickness gauge;
[0080] Alcohol resistance: Spray the same amount of 75% alcohol on the surface of the glove and observe whether the glove shows any deformation or damage;
[0081] Hydrogen peroxide resistance: tested according to EN374 standard.
[0082] Tensile strength: tested according to ASTM D412 standard;
[0083] 100% Modulus: Tested according to ASTM D412 standard;
[0084] 300% Modulus: Tested according to ASTM D412 standard;
[0085] Elongation: Tested according to ASTM D412 standard;
[0086] Pass rate: Prepare 1000 glove samples and fill them with water. The M size gloves are required to be filled with 500g of water. After three minutes, observe whether the gloves leak water. If they leak water, they are judged as unqualified.
[0087] Example
[0088] Example 1
[0089] I. Raw material preparation:
[0090] 1. Preparation of flocculant raw materials:
[0091] Take 100 kg of the above-mentioned release agent raw material SD-6, 200 kg of coagulant calcium nitrate, 120 kg of crosslinking agent CYMEL-385, 1578.2 kg of deionized water, 1 kg of wetting agent TERIC-320, and 0.8 kg of defoamer DF-38, stir thoroughly and filter for later use.
[0092] 2. Preparation of water-based latex raw materials:
[0093] Take 1028 kg of waterborne polyurethane 7566, 2kg Shiming blue paste S19-LR03, 20kg Shiming titanium dioxide paste, 1kg wetting agent TERIC-320, 949kg deionized water, mix thoroughly and filter for later use.
[0094] 3. Preparation of anti-stick coating materials:
[0095] Take 200 kg of commercially available YMT-D2103 from Umetech (Beijing) Environmental Materials Technology Co., Ltd., and 1800 kg of deionized water, stir thoroughly, and then filter for later use.
[0096] II. Preparation of polyurethane gloves:
[0097] 1. Impregnating flocculant
[0098] Add the flocculant raw material of the above composition to tank A and keep stirring; add the water-based latex raw material to tank B and keep stirring; add the anti-stick coating raw material to tank C and keep stirring; the stirring rate is 400 r / min.
[0099] The hand mold was sequentially cleaned with a brush in an acid tank (6wt% nitric acid aqueous solution; 70℃), a brush in an alkali tank (7wt% sodium hydroxide aqueous solution; 70℃), a brush in a clean water tank 1 (70℃), and then heated in a clean water tank 2 (80℃). After treatment, it was placed in an oven D (set temperature 80℃) and baked for 1.5 minutes. After removing it from the oven D, when the hand mold temperature was 60℃, it was immersed in a tank A containing the above-mentioned flocculant raw materials and ran in the tank for 10 seconds. The hand mold was then removed and rotated to evenly distribute the excess flocculant before being placed back into the oven D and baked for 2 minutes.
[0100] 2. Impregnation with latex
[0101] After baking in oven D, the hand mold is cooled to 65°C and then immersed in tank B containing the above-mentioned water-based latex raw material. It runs in tank B for 20 seconds, then the hand mold is removed and rotated to evenly distribute the excess latex before being placed back into oven D for baking for 2 minutes. After baking, the hand mold is sequentially immersed in filtration tanks 1, 2, and 3, which are set at 60°C. The immersion time in each tank is 15 seconds, and the total time is 45 seconds. After filtration, the hand mold is moved to the next stage oven D for baking for 2 minutes.
[0102] 3. Impregnate with anti-stick coating
[0103] After baking in oven D, the hand molds are sequentially immersed in tank C containing the aforementioned anti-stick coating material for 10 seconds, with the immersion height 2 cm below the glove film. After exiting tank C, the hand molds are placed in oven D for baking for 2 minutes. Then, they are placed in the edge rolling machine and rolled to the height of the coating. The hand molds are then placed in oven F and baked at temperatures of 120℃, 125℃, and 130℃ for 5 minutes, 10 minutes, and 10 minutes respectively. After baking, they are immersed in expansion tank G. After exiting tank G, they are demolded, washed with pure water to remove dust, dried, and then subjected to air leakage testing and physical property testing.
[0104] Example 2
[0105] I. Raw material preparation:
[0106] 1. Preparation of flocculant raw materials:
[0107] Take 100 kg of the above-mentioned release agent raw material SD-6, 200 kg of coagulant calcium nitrate, 80 kg of crosslinking agent CYMEL-385, 1618.2 kg of deionized water, 1 kg of wetting agent TERIC-320, and 0.8 kg of defoamer DF-38, stir thoroughly and filter for later use.
[0108] 2. Preparation of water-based latex raw materials:
[0109] Take 1028 kg of waterborne polyurethane 7566, 2kg Shiming blue paste S19-LR03, 20kg Shiming titanium dioxide paste, 1kg wetting agent TERIC-320, 949kg deionized water, mix thoroughly and filter for later use.
[0110] 3. Preparation of anti-stick coating materials:
[0111] Take 200 kg of commercially available YMT-D2103 from Umetech (Beijing) Environmental Materials Technology Co., Ltd., and 1800 kg of deionized water, stir thoroughly, and then filter for later use.
[0112] II. Preparation of polyurethane gloves:
[0113] 1. Impregnating flocculant
[0114] Add the flocculant raw material of the above composition to tank A and keep stirring; add the water-based latex raw material to tank B and keep stirring; add the anti-stick coating raw material to tank C and keep stirring; the stirring rate is 400 r / min.
[0115] The hand mold was cleaned under the same conditions as in Example 1. After processing, it was placed in oven D (set temperature 80°C) and baked for 1.5 minutes. After removing it from oven D, when the hand mold temperature was 60°C, it was immersed in tank A containing the above-mentioned flocculant raw materials and ran in the tank for 10 seconds. The hand mold was then removed and rotated to evenly distribute the excess flocculant before being placed in oven D and baked for 2 minutes.
[0116] 2. Impregnation with latex
[0117] After baking in oven D, the hand mold is cooled to 60°C and then immersed in tank B containing the above-mentioned water-based latex raw material. It runs in tank B for 20 seconds, then the hand mold is removed and rotated to evenly distribute the excess latex before being placed in oven D for baking for 2 minutes. After baking, the hand mold is immersed in filtration tanks 1, 2, and 3, which are set at 60°C. The immersion time in each tank is 15 seconds, and the total time is 45 seconds. After filtration, the hand mold is moved to the next stage oven D for baking for 2 minutes.
[0118] 3. Impregnate with anti-stick coating
[0119] After baking in oven D, the hand molds are sequentially immersed in tank C containing the aforementioned anti-stick coating material for 10 seconds, with the immersion height 2 cm below the glove film. After exiting tank C, the hand molds are placed in oven D for baking for 2 minutes. Then, they are placed in the edge rolling machine and rolled to the height of the coating. The hand molds are then placed in oven F and baked at temperatures of 120℃, 125℃, and 130℃ for 5 minutes, 10 minutes, and 10 minutes respectively. After baking, they are immersed in expansion tank G. After exiting tank G, they are demolded, washed with pure water to remove dust, dried, and then subjected to air leakage testing and physical property testing.
[0120] Comparative Example 1
[0121] I. Raw material preparation:
[0122] 1. Preparation of flocculant raw materials:
[0123] Same as Example 1, except that the crosslinking agent in the flocculant raw material is replaced with an equal amount of deionized water.
[0124] 2. Preparation of water-based latex raw materials:
[0125] Same as Example 1, except that: 120 kg of crosslinking agent is added to the water-based latex raw material, and an equal weight of deionized water is removed.
[0126] 3. Preparation of anti-stick coating materials:
[0127] Same as Example 1.
[0128] II. Preparation of polyurethane gloves:
[0129] Same as in Example 1. The gloves were then subjected to physical property testing.
[0130] Comparative Example 2
[0131] I. Raw material preparation:
[0132] 1. Preparation of flocculant raw materials:
[0133] Same as Example 2, except that an equal amount of Covestro's blocked curing agent Imprafix 2794XP was used as the crosslinking agent.
[0134] 2. Preparation of water-based latex raw materials:
[0135] Same as Example 2.
[0136] 3. Preparation of anti-stick coating materials:
[0137] Same as Example 2.
[0138] II. Preparation of polyurethane gloves:
[0139] Same as Example 2, except that the baking temperature is changed to 120℃, 130℃, and 140℃ for stepped baking.
[0140] The physical property test results of the polyurethane gloves obtained in the above embodiments and comparative examples are shown in Table 1 below:
[0141] Table 1. Glove Physical Property Test Table
[0142]
[0143] Note: For performance ratings from 1 to 5, 1 is the worst and 5 is the best.
[0144] Compared with Example 1, adding the crosslinking agent to the flocculant significantly reduced edge cracking, while the durability remained unchanged. This is mainly because the crosslinking agent in the latex reacts with the latex and self-crosslinks as the number of dipping cycles increases, leading to a local increase in the molecular weight of the latex. Uneven stress shrinkage at the edge causes cracking. Furthermore, due to leaching during the glove molding process, some crosslinking agent migrates from the film into the aqueous phase, resulting in poor alcohol resistance of the final glove.
[0145] Compared with Comparative Example 2 and Example 2, a closed-type curing agent was used and the baking temperature was increased, but the final crosslinking effect was poor, especially in terms of alcohol resistance; the gloves broke upon contact with alcohol.
[0146] Based on comprehensive comparison, selecting etherified amino resin crosslinking agents and blending the crosslinking agents with flocculants is the most suitable method for the stable production of polyurethane gloves with a high pass rate.
Claims
1. A polyurethane composition comprising: (1) Flocculant raw materials, by weight, include: 1-6 parts release agent; 5-20 parts of coagulant; 4-15 parts of etherified amino resin crosslinking agent; 55-81 parts pure water; (2) Water-based latex raw materials, by weight, include: 40-60 parts of waterborne polyurethane; 40-60 parts water; (3) Anti-stick coating, by weight, includes: 5-10 parts of anti-sticking mortar; 75-95 parts water.
2. The composition according to claim 1, wherein, The release agent is selected from one or more of paraffin-based release agents, calcium stearate-based release agents, and high-molecular-weight silicone release agents; The coagulant is selected from one or more of calcium nitrate, calcium chloride, and aluminum nitrate; The crosslinking agent is selected from one or more of the amino resin crosslinking agents CYMEL-385 and CYMEL-325 from Cytec Corporation.
3. The composition according to claim 1, wherein, The flocculant raw material also includes: 0.02-0.1 parts of wetting agent and / or 0.01-0.15 parts of defoamer.
4. The composition according to claim 3, wherein, The defoamer is selected from one or more of mineral oil defoamers and surfactant defoamers.
5. The composition according to claim 1, wherein, The water-based latex raw material also includes: 0.02-0.15 parts of color paste, 1-5 parts of titanium dioxide paste, and 0.02-0.1 parts of wetting agent.
6. The composition according to claim 5, wherein, The colorant is a blue colorant, a black colorant, or a green colorant.
7. The composition according to claim 1, wherein, The waterborne polyurethane in the waterborne latex raw material is an aliphatic waterborne polyurethane and / or an aromatic waterborne polyurethane.
8. The composition according to claim 7, wherein, The solid content of the waterborne polyurethane is 30-50%.
9. The composition according to claim 7 or 8, wherein, The isocyanate used in the preparation of the waterborne polyurethane is selected from one or more of 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, and toluene diisocyanate; the polyol is selected from one or more of 1,6-hexanediol phthalic anhydride polyester polyol, polybutylene adipate, polypentyl adipate, and polycarbonate diol.
10. The composition according to claim 7, wherein, The waterborne polyurethane in the waterborne latex raw material is selected from: Wanhua Chemical's Tekspro® 7566, Tekspro® 7351, Leasys® 3458, Leasys® 3978 and Leasys® 3979.
11. The composition according to claim 1, wherein, The anti-sticking paste is selected from one or more of water-based polyurethane or water-based acrylic glove inner coatings.
12. A method for preparing a disposable polyurethane glove, comprising the following steps: 1) Add the flocculant raw material of the composition according to any one of claims 1-11 to material tank A and keep stirring; add the aqueous latex raw material to material tank B and keep stirring; add the anti-sticking coating raw material to material tank C and keep stirring. 2) After cleaning the hand mold, put it into the oven D for baking. After it comes out of the oven, cool it down to a certain temperature and immerse it in the material tank A to keep it moving forward steadily. After exiting the material tank A, the hand mold moves into the oven D for baking. 3) After the hand mold finishes baking in oven D, it is cooled down and then immersed in material tank B to maintain stable operation. After exiting material tank B, the hand mold moves to oven D for baking. After baking until the film is surface dry, it moves into the filtration tank E to maintain stable operation. After exiting filtration tank E, the hand mold enters oven D for baking. 4) After the hand mold is baked in oven D, it is immersed in material tank C and kept running smoothly. After exiting material tank C, the hand mold enters oven D for baking. After baking, the edges are rolled up and it continues to run into oven F for baking. 5) After the hand mold is baked in oven F, it continues to be immersed in expansion tank G. After exiting tank G, it is demolded, washed with pure water to remove dust, dried, and then packaged into boxes.
13. The method according to claim 12, wherein, In step 1), the stirring rate is 300-500 r / min.
14. The method according to claim 12, wherein, In step 2), the temperature of oven D is 50-100℃, the baking time in oven D before the hand mold enters material tank A is 1-5 minutes, the temperature when the hand mold is immersed in material tank A is 50-75℃, the total running time in material tank A is 5-15 seconds, and the baking time in oven D after exiting material tank A is 1-5 minutes.
15. The method according to claim 12, wherein, In step 3), the temperature of the hand mold when it is immersed in the material tank B is 50-75℃, the total running time in the material tank B is 15-35s, the baking time in the oven D after exiting the material tank B is 1-5min, the total running time in the filtration tank is 10-60s, and the baking time in the oven D after exiting the filtration tank is 1-5min.
16. The method according to claim 15, wherein, In step 3), the filtration tank has cooling and heating functions, is filled with pure water, and has 2-5 filtration tanks. The water temperature is independently set to 50-70℃, and the calcium ion content of each filtration tank is kept below 1000ppm.
17. The method according to claim 12, wherein, In step 4), when immersing in the material tank C, the liquid level is 1-2 cm lower than the film. The total running time in the material tank C is 3-10 seconds, and the baking time in the oven D is 1-5 minutes. The edge is rolled up to the position of the coating. The temperature of the oven F is set to 120-145℃.
18. The method according to claim 17, wherein, The baking in oven F uses a stepped temperature setting with a temperature gradient of 5-20℃, and the total baking time in oven F is 25-30 minutes.
Citation Information
Patent Citations
Coagulant-free waterborne polyurethane emulsion for impregnating labor protection appliances, and preparation method thereof
CN113736061A
Composition and method for preparing polyurethane gloves by using composition
CN116063885A